Modern Trends in the Digitalization of Higher Physical Education in China - RUI, Chen (Educological discourse, 2025)
This article provides an in-depth analysis of the ongoing digital transformation in higher physical education (HPE) within China, exploring how various digital technologies are reshaping traditional physical education practices. The Chinese government’s active role in promoting digitalization through initiatives such as the Education Informatization 2.0 Action Plan has significantly accelerated the integration of online learning platforms, wearable devices, and immersive technologies like virtual reality (VR) and augmented reality (AR) in HPE. This article delves into how these technologies are applied in educational settings, from online platforms that allow asynchronous learning to wearable devices that facilitate real-time tracking of physical activity and physiological metrics. The study underscores the practical advantages of these digital tools, including increased student engagement, personalized learning experiences, and broader accessibility to physical education resources. Online learning platforms have enabled remote instruction and access to theoretical knowledge, a trend that grew substantially during the COVID-19 pandemic. These platforms allow students to engage with a mix of instructional content, including multimedia resources, live demonstrations, and discussion forums. The study presents examples, such as Tsinghua University’s “Rain Classroom”, which integrates social media to enhance interaction and accessibility. Wearable devices, such as fitness trackers, are highlighted as transformative tools in HPE. These devices offer data-driven insights into students’ physical activities, allowing for more personalized instruction and targeted feedback. The article discusses case studies, including Beijing Sport University’s initiative to incorporate wearable technology into classes, which has resulted in greater student motivation and performance tracking. Additionally, VR and AR technologies are explored for their potential to provide safe, controlled, and immersive environments that simulate real-life physical activities. These technologies are particularly valuable for teaching complex movements and skills that require visualization and practice in a risk-free setting. For example, VR applications used in teaching sports like skiing allow students to experience and understand movements virtually before attempting them physically. Despite the many benefits, the study also identifies several critical challenges that hinder the full potential of digitalization in HPE. The digital divide remains a significant concern, with disparities in access to digital resources among students from various socioeconomic backgrounds. The article stresses the importance of equitable access to these resources, as rural and lowincome students may lack reliable internet or suitable devices for participation. Additionally, the study emphasizes the need for educator training and professional development, as many physical education teachers lack digital literacy or are resistant to new technologies. Data privacy and security issues are another significant challenge, particularly with the collection and use of personal and health data from wearable devices and online platforms. The article calls for robust policies to protect student information and maintain trust in digital learning environments. The article concludes by recommending a blended learning model for HPE, combining online theoretical instruction with inperson practical training to balance the benefits of both digital and traditional methods. It suggests that investments in technology infrastructure, ongoing research, and collaborations between educational institutions and government agencies are crucial to addressing these challenges and ensuring the successful digital transformation of HPE.